1997
DOI: 10.1016/s0002-9149(97)00008-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Severity of Coronary Artery Stenosis and the Collateral Circulation on the Functional Outcome of Dyssynergic Myocardium After Revascularization in Patients With Healed Myocardial Infarction and Chronic Left Ventricular Dysfunction

Abstract: The aim of this study was to assess the influence of the severity of coronary artery stenosis and the grade of collateral circulation on myocardial viability in patients with chronic left ventricular (LV) dysfunction undergoing coronary artery bypass grafting. Forty patients (age 59 { 8 years) with old myocardial infarction were studied by dobutamine stress echocardiography (DSE) before coronary artery bypass grafting. LV function was assessed using a 16-segment, 5-grade score model. Viability and functional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Left ventricular recovery occurred in 27% of patients, a proportion similar to previous studies with a comparable set of patients [11, 18, 19]. However, most previous studies are devoid of any angiographic follow-up information about restenosis or reocclusion and the relation to functional recovery [18, 19, 20, 21].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Left ventricular recovery occurred in 27% of patients, a proportion similar to previous studies with a comparable set of patients [11, 18, 19]. However, most previous studies are devoid of any angiographic follow-up information about restenosis or reocclusion and the relation to functional recovery [18, 19, 20, 21].…”
Section: Discussionsupporting
confidence: 78%
“…However, most previous studies are devoid of any angiographic follow-up information about restenosis or reocclusion and the relation to functional recovery [18, 19, 20, 21]. In the current study, left ventricular recovery only occurred in patients with successful revascularization and unrestricted perfusion at follow-up.…”
Section: Discussionmentioning
confidence: 59%
“…These findings might be considered as indirect evidences demonstrating the beneficial effects of CCC on LV systolic function [17]. There have been studies [5,9,18,19] demonstrating the absence of relationship between LV systolic function and CCC, whereas some studies demonstrated a weak relationship [20], or a close relationship [8,10,21], between these two parameters. The discordance in the results of the previous studies might be due, in part, to the inclusion of a nonuniform patient population, often with multivessel coronary artery disease or various degrees of incomplete coronary occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary collateral circulation (CCC) usually supplies basal level of perfusion to the ischemic myocardium and maintains the tissue viability [2,3]. Despite shortcomings of the data concerning the relationship between CCC and myocardial viability, CCC does not generally appear to perfuse the nonviable myocardial tissue [4][5][6]. Conflicting studies exist concerning the functional importance of CCC [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, dobutamine-induced wall motion worsening in myocardial territories supplied by occluded epicardial vessels has been reported in case of evident collateral circulation [38], thus emphasizing the importance of a preserved, though reduced, blood flow to distinguish jeopardized myocardium from necrotic tissue. Differently, the ability of low-dose dobutamine stimulation to identify myocardial regions with a high probability of functional improvement after revascularization seems to be independent of both severity of underlying coronary stenosis and degree of collateralization of the involved coronary vessel [39]. …”
Section: Target Of Ultrasound Diagnosis: the Present And The Futurementioning
confidence: 99%